Study protocol for endoscopic ultrasonography-guided ethanol injection therapy for patients with pancreatic neuroendocrine neoplasm: a multicentre prospective study. Issue 7 (12th July 2021) - Matsumoto, Kazuyuki; Kato, Hironari; Kitano, Masayuki; Hara, Kazuo; Kuwatani, Masaki; Ashida, Reiko; Takenaka, Mamoru; Yamazaki, Tatsuhiro; Sakurai, Jun; Yoshida, Michihiro; Okada, Hiroyuki
Abstract : Introduction: The management of small pancreatic neuroendocrine neoplasms (PNENs) remains controversial. The standard treatment for PNENs is surgical resection; however, invasiveness of surgical procedure remains higher and the incidence of postoperative adverse events is still high. Recently, the efficacy and safety of endoscopic ultrasonography (EUS)-guided ethanol injection for small PNENs has been preliminarily demonstrated. Thus, a multicentre prospective study is being conducted to evaluate the efficacy and safety of EUS-guided ethanol injection therapy for small PNENs. Methods and analysis: The major eligibility criteria are the presence of pathologically diagnosed grade (G) 1 tumour, a tumour size of ≤15 mm and non-functional PNEN or insulinoma. For treatment, we will use a 25-gauge needle and pure ethanol. Contrast-enhanced CT (CE-CT) will be performed on postoperative day 3–5, and if enhanced areas of the tumour are still apparent, an additional session is scheduled during the same hospitalisation period. We set the total amount of ethanol per session to 2 mL. To evaluate the efficacy and safety, CE-CT will be performed at 1 and 6 months after treatment. The primary endpoint is the percentage of subjects who achieved all of the following evaluated points. Efficacy will be evaluated based on the achievement of complete ablation (defined as no enhanced area within the tumour on CE-CT) at 1 and 6 months. Safety will be evaluated based on the avoidance of severe adverse events within 1 month after treatment, continuing severe pancreatic fistula at 1 month after treatment and the incidence and/or exacerbation of diabetes mellitus at 6 months after treatment. Ethics and dissemination: This protocol has been approved by Okayama University Certified Review Board (approval number. CRB19-007). The results will be submitted to peer-reviewed journals and will be presented at international conferences. Trial registration number: jRCTs061200016.